User-friendly street in Malaysia - Abdul Rahman, Norhafizah (2014)
There has been a growing concern in Malaysia towards promoting streets that are friendly to all users due to the streets environment which are perceived as not friendly to pedestrians. Based on previous research, nowadays, people are more ready to walk than before if streets are improved to meet the needs of the users. The aim of this research is to identify the factors and attributes that make a street friendly to the users. The research employed a mixed methodology using a case study approach. Jalan Tuanku Abdul Rahman, as one of the main urban commercial streets in city centre of Kuala Lumpur was selected based on the physical, functional and socio-cultural characteristics of the street. A sample survey and in-depth interview were conducted with residents of Kuala Lumpur city centre. This was supported by field observations using scheduled checklists, photos and maps procedures. Analysis was conducted by means of triangulation. The research has found that the factors that affect the level of friendliness of streets to the users are attractiveness, activities, congestions, proximity and familiarity. The findings also indicate five supportive factors that affect the level of friendliness of the street; public space, greenery/trees, maintenance, public amenities and freedom of action. There are three main qualities that affect the level of friendly-street; safety and security; comfort and convenience, and accessibility. Based on the research done, safety and security are the most important qualities that contribute to the user-friendly urban commercial street; it is followed by comfort and convenience and accessibility. There is also a difference between the level of importance of attributes between different types of user, age groups and distance from place of residence to the user-friendly streets. It is found that the level of importance of factors and attributes is different from previous research. These findings contribute the gap in the knowledge concerning the most important needs and users' perception of a friendly urban commercial street based on the situation in Malaysia which has a different climate, social activities and cultural context from other previous researches.